2013
DOI: 10.1111/psyp.12154
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potentials reveal the effect of prior knowledge on competition for representation and attentional capture

Abstract: Objects compete for representation in our limited capacity visual system. We examined how this competition is influenced by top-down knowledge using event-related potentials. Competition was manipulated by presenting visual search arrays in which the target or distractor was the only color singleton compared to displays in which both singletons were presented. Experiments 1 and 2 manipulated whether the observer knew the color of the target in advance. Experiment 3 ruled out low-level sensory explanations. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 43 publications
(144 reference statements)
8
45
0
Order By: Relevance
“…To this end, the target is placed directly above or below central fixation so that no lateralized ERP results, and the distractor is placed on the left or right so that an N2pc will indicate whether the distractor has been selected. An N2pc to a salient-but-irrelevant stimulus has been reported (Burra & Kerzel, 2013;Hickey et al, 2006;Hilimire & Corballis, 2014;Kiss, Grubert, Petersen, & Eimer, 2012), suggesting that attention does indeed move to the most salient element.…”
Section: Conditions Resulting In Attentional Capture or Suppressionmentioning
confidence: 98%
See 1 more Smart Citation
“…To this end, the target is placed directly above or below central fixation so that no lateralized ERP results, and the distractor is placed on the left or right so that an N2pc will indicate whether the distractor has been selected. An N2pc to a salient-but-irrelevant stimulus has been reported (Burra & Kerzel, 2013;Hickey et al, 2006;Hilimire & Corballis, 2014;Kiss, Grubert, Petersen, & Eimer, 2012), suggesting that attention does indeed move to the most salient element.…”
Section: Conditions Resulting In Attentional Capture or Suppressionmentioning
confidence: 98%
“…We recently suggested that the trial context may explain the different results (Burra & Kerzel, 2013). Attentional capture (i.e., an N2pc to the distractor) was observed when target and nontarget shapes swapped roles randomly from trial to trial and behavioral interference was large (Burra & Kerzel, 2013;Hickey et al, 2006;Hilimire & Corballis, 2014;Kiss et al, 2012). In contrast, attentional suppression (i.e., a P D to the distractor) occurred reliably when the target was fixed and interference from the distractor was small (Burra & Kerzel, 2013;Jannati et al, 2013).…”
Section: Conditions Resulting In Attentional Capture or Suppressionmentioning
confidence: 99%
“…104 Accordingly, the Pd has been proposed to reflect a mechanism that prevents or terminates the allocation of attention toward a salient distractor. 10,105 Although in many cases the Pd follows the N2pc 76,102,[106][107][108] or N1pc 104 in the ERP waveform as predicted by the ignoring paradox, growing evidence indicates that salient distractors can also be inhibited (as evidenced by a Pd) in the absence of any neural evidence for attentional selection (e.g., the absence of an N2pc). 10 Notably, in the majority of these studies, the experimental design allowed for statistical learning, either because the target and distractor identities were fixed (i.e., same color/shape) across trials, 94,101,109,110 or because there was a high probability distractor location.…”
Section: First Trial Last Trialmentioning
confidence: 99%
“…N2pc amplitude has also been used as a measure of attentional capture by relevant stimuli (Kiss, Jolicoeur, Dell'Acqua, & Eimer, 2008), or pop-out objects (Eimer & Kiss, 2007;Holgian, Doallo, Vizoso, & Cadaveira, 2009). In the WORKING MEMORY AVAILABILITY AFFECTS DISTRACTOR PROCESSING 5 present study, we took advantage of the contralateral control method in order to measure the N2pc elicited separately by targets and distractors (Hickey, Di Lollo, & McDonald, 2009;Hilimire & Corballis, 2014;Hilimire, Mounts, Parks, & Corballis, 2011). This method provided us with independent measures of N2pc to targets, reflecting target selection, and N2pc to distractors, reflecting initial distractor capture.…”
Section: Introductionmentioning
confidence: 99%